Anti-inflammatory labdane diterpenoids from Leonurus japonicus Houtt. (May 2020) - Yang, Biao; Hu, Yumei; Cheng, Ningbo; Su, Zhenzhen; Zhong, Yan; Cao, Zeyu; Cao, Liang; Huang, Wenzhe; Wang, Zhenzhong; Xiao, Wei
Abstract: Seven undescribed labdane diterpenoids, japonicones A-G, were isolated from the aerial parts of Leonurus japonicus Houtt. Japonicones C-G contained two keto carbonyl groups in their structures attached to C-3 and C-7, which are rare for labdane diterpenoids. The structures and absolute configurations of japonicones A-G were established by means of spectroscopic analyses (HRESIMS, 1D and 2D NMR, and ECD). Their anti-inflammatory activities were evaluated by measuring their inhibitory effects on PGE2 production in LPS-stimulated RAW264.7 macrophages. Japonicones A-D and G showed inhibition of PGE2 production with IC50 values in the range of 8.62–30.71 μ M (the positive control paracetamol showed an IC50 = 5.79 μ M). Graphical abstract: Image 1 Highlights: Seven undescribed labdane diterpenoids were isolated from the aerial parts of Leonurus japonicus Houtt. Their structures and absolute configurations were established by means of spectroscopic analyses. Compounds 1 −4, and 7 showed inhibition of PGE2 production with IC50 values in the range of 8.62−30.71 μ M.